A Case of Neuroleptic Malignant Syndrome in a Profoundly Intellectually Disabled Patient with Successful Reintroduction of Antipsychotic Therapy with Quetiapine - Patel, Kamal; Lilly, Brandon; Ajayi, Oluwadamilare; Melvin, Kelly (Case Reports in Psychiatry, 2018)
Neuroleptic Malignant Syndrome (NMS) is a rare condition clinically characterized by muscle rigidity, hyperthermia, autonomic instability, and acute mental status change. NMS is most often associated with use of high-potency first-generation antipsychotic medications; though, other neuroleptics have been implicated as well. NMS can be fatal with estimated mortality rates as high as 20%. Patients experiencing certain severe complications, including renal failure, have been associated with mortality as high as 50%, stressing the need for early recognition and treatment. Here we present the case of a 54-year-old male that initially presented with symptoms suspicious for sepsis, but who eventually developed a clinical picture consistent with NMS. We describe the diagnostic and treatment process leading to symptom remission. We then discuss our decision to reintroduce an atypical antipsychotic agent, quetiapine. This case illustrates the importance of early recognition of the signs and symptoms of NMS and the need to initiate treatment promptly in order to prevent complications, including death. This case also highlights the decision to resume antipsychotic pharmacotherapy after adequate resolution of NMS, demonstrating that it can be done so safely if started at low doses coupled with intensive monitoring of the patient.